Integration of Coding and Artificial Intelligence Based on Tri-N to Enhance Learning Outcomes in Science and Social Studies for Elementary School Students - Lukman Setiawan; Akbar Al Masjid; Ana Fitrotun Nisa; Elyas Djufri (Green Publisher Indonesia, 2026)
Low learning outcomes in the Integrated Science (IPAS) subject at the elementary school level highlight the need for innovative, technology-enhanced learning approaches. This study aims to improve sixth-grade students' IPAS achievement by implementing a learning design that integrates coding and artificial intelligence within the Tri-N approach (niteni, nirokke, nambahi). The novelty of this research lies in the systematic integration of Tri-N—a culturally-rooted pedagogical framework—with modern computational tools (coding and AI), creating a unique bridge between local wisdom and 21st-century digital competencies in elementary education. Conducted at SDN 2 Cikalongwetan, West Bandung Regency, the research involved 40 students and employed Classroom Action Research using Kurt Lewin’s two-cycle model. Each cycle consisted of planning the Tri-N–based coding–AI design, implementing learning activities, observing student engagement, and reflecting on outcomes for improvement. Data were collected through observations, interviews, documentation, and learning achievement tests, and analyzed using descriptive quantitative and qualitative techniques. The study found a steady increase in students’ average scores from 73.6 (pre-action) to 78.9 (Cycle I) and 84.5 (Cycle II), achieving 100% mastery. Qualitative results also showed enhanced learning activeness, computational thinking, and creativity, particularly during the Nambahi stage. The findings demonstrate that integrating coding and AI supports interactive, adaptive, and meaningful learning experiences while strengthening conceptual understanding and participation. This study suggests that the Tri-N–based coding–AI learning design is a strategic alternative for supporting the Merdeka Curriculum and improving technological literacy in elementary schools.